Revision of Thraulus Eaton 1881 (Ephemeroptera: Leptophlebiidae: Choroterpinae) - Grant, Peter M. (Zootaxa, 2024)
The genus Thraulus is widespread throughout much of the Eastern Hemisphere. Since Eaton established Thraulus in 1881, 62 species have, at one time or another, been placed in this genus. Thirty-eight of those species were eventually moved to other genera. Any comprehensive study of the remaining species, based on the published literature, is difficult as they were described by many authors, using different criteria, over a period of 142 years. The purpose of this study was to redescribe this genus, based on previously described species and nine new species, and to provide a format for future taxonomic and morphological studies of Thraulus. Redescriptions of most species were based on direct examination of external morphological characters. Descriptions or diagnoses of species, whose types were unavailable for study, were made using the original published description and additional information provided by authors of several of those species. The following species were studied: Thraulus amravati Vasanth, Subramanian & Selvakumar, 2022; T. bellus Eaton, 1881; T. bishopi Peters & Tsui, 1972; T. cuspidatus Vasanth, Subramanian & Selvakumar, 2022; T. demoulini Peters & Tsui, 1973; T. fasciatus (Kimmins, 1956); T. fatuus Kang & Yang, 1994; T. femoratus Li, Liu & Zhou, 2006; T. gopalani Grant & Sivaramakrishnan, 1985; T. jacobusi Isack, Srinivasan, Sivaruban & Barathy, 2022; T. macilentus Kang & Yang, 1994; T. malabarensis Vasanth, Subramanian & Selvakumar, 2022; T. mudumalaiensis Soman, 1991; T. plumeus Selvakumar, Vasanth & Subramanian, 2022; T. semicastaneus (Gillies, 1951); T. thiagarajani Balasubramanian & Muthukatturaja, 2019; T. thraker Jacob, 1988; T. torrentis (Gillies, 1964); T. turbinatus (Ulmer, 1909); T. umbrosus Kang & Yang, 1994; and T. vellimalaiensis Vasanth, Subramanian & Selvakumar, 2022. Nine new species of Thraulus are described: T. connubialis sp. nov., Malaysia; T. cursus sp. nov., Japan; T. eatoni sp. nov., Indonesia; T. ishiwatai sp. nov., Japan; T. madagasikarensis sp. nov., Madagascar; T. nihonensis sp. nov., Japan; T. opifer sp. nov., Australia; T. parentalis sp. nov., Malaysia; and T. petersorum sp. nov., Malaysia. Thraulus can be distinguished from all other genera of Leptophlebiidae by the following combination of characters: In the imagos, 1) upper portion of eyes oval-suboval, major axes diverge anteriorly; 2) vein MA fork of fore wings symmetrical; 3) vein MP fork of fore wings asymmetrical—a cross vein connects base of MP2 to MP1, MP fork closer to base of wing than Rs fork; 4) strongly oblique cross vein extends between veins R4+5 and MA1 just apical to fork of vein MA; 5) 2 cubital intercalary veins in fore wings; 6) costal projection on hind wings well-developed, bluntly rounded to acutely pointed; 7) claws dissimilar—one blunt and pad-like, the other apically hooked; 8) penes long, relatively straight, narrow, parallel, usually contiguous mesally but not fused, apex may have lateral projections; 9) sternum 7 of female with posterior margin straight or shallowly concave or convex mesally; and 10) sternum 9 of females rounded apically. In addition, penile spines occur on most species. In the nymphs, 1) lateral margins of clypeus parallel; 2) width of labrum subequal to width of clypeus; 3) 2 dorsal rows of setae on labrum; 4) venter of labrum with 1 row of short stout setae on either side of midline near anterior margin, rows curve mesally; 5) hypopharynx with small, rounded, posterolateral projections on arms of superlingua; 6) large spine on posterolateral corners of terga 6–9, 7–9 or 8–9; 7) gills 1–7 dissimilar: gill 1 composed of 1 or 2 subulate lamellae or a dorsal subulate lamella and a ventral fimbriate oval lamella, and gills 2–7 composed of dorsal and ventral oval lamellae with fimbriate margins. Two species continue to be nomen dubium—T. siewertii (Weyenbergh, 1883) and T. vogleri (Weyenbergh, 1883). Thraulus grandis Gose, 1980 is considered nomen nudum. A review of published phylogenetic studies involving Thraulus is provided. With the species discussed in this paper, along with reports of additional new species to be described, Thraulus has the potential to be included among the more specious genera of Ephemeroptera.